DEFINITION OF AERODYNAMIC CHARACTERISTICS OF THE PROFILE UNDER THE DRAG POLAR OF THE FINITE WING - B. L. Artamonov (Научный вестник МГТУ ГА, 2016)
The numerical method of calculation of aerodynamic characteristics of a profile is stated on the basis of the experiment of aerodynamic characteristics of a rectangular wing of a final lengthening. The problem is solved by a method consecutive approximation with the use of a matrix of private derivative factors of elevating force and aerodynamic resistance of a wing under the appropriate characteristics of a profile.